2018
DOI: 10.1021/acs.jchemed.8b00096
|View full text |Cite
|
Sign up to set email alerts
|

ConfChem Conference on Mathematics in Undergraduate Chemistry Instruction: MUST-Know Pilot Study—Math Preparation Study from Texas

Abstract: This report summarizes one of the invited papers to the ConfChem online conference on Mathematics in Undergraduate Chemistry Instruction, held from October 23 to November 27, 2017, and hosted by the ACS DivCHED Committee on Computers in Chemical Education (CCCE). Combining data collected by a team of nine instructors from six Texas institutions for an IRB-approved investigation, this research correlated the arithmetic skills of first-year general chemistry students (n = 2127) to final course grades. The valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 0 publications
1
14
0
2
Order By: Relevance
“…Bahkan tingkat kesulitan siswa kelompok bawah mencapai 65,7% dengan kategori tinggi. Temuan ini bisa dipahami dan sekaligus sebagai petunjuk bahwa pembelajaran kimia, dalam hal ini penentuan pH larutan garam hasil hidrolisis, tidak hanya memerlukan pemahaman, tetapi juga memerlukan strategi metakognisi (Aleven & Koedinger, 2002) dan kecerdasan matematika (Albaladejo et al, 2018).…”
Section: Pembahasan Tingkat Kesulitan Bahan Kajian Hidrolisis Garamunclassified
See 1 more Smart Citation
“…Bahkan tingkat kesulitan siswa kelompok bawah mencapai 65,7% dengan kategori tinggi. Temuan ini bisa dipahami dan sekaligus sebagai petunjuk bahwa pembelajaran kimia, dalam hal ini penentuan pH larutan garam hasil hidrolisis, tidak hanya memerlukan pemahaman, tetapi juga memerlukan strategi metakognisi (Aleven & Koedinger, 2002) dan kecerdasan matematika (Albaladejo et al, 2018).…”
Section: Pembahasan Tingkat Kesulitan Bahan Kajian Hidrolisis Garamunclassified
“…Langkah ini merupakah langkah tersulit dari keseluruhan langkah penyelesaian soal-soal hidrolisis garam yang dimulai dari penulisan reaksi ionisasi garam, menentukan spesi ion yang mengalami hidrolisis, menentukan @ 2020 J-PEK, Jurnal Pembelajaran Kimia, 5(1), 32-39 konsentrasinya, menentukan konsentrasi ion H + yang dihasilkan dan yang terakhir menghitung pH-nya. Penyelesaian soal ini memerlukan pemahaman konsep-konsep garam, hidrolisis garam dan kekuatan asam-basa yang baik, strategi metakognisi (Aleven & Koedinger, 2002) dan keterampilan matematika kimia (Albaladejo et al, 2018). Oleh karena itu wajar apabila tingkah kesulitan rata-rata siswa berada pada kategori sedang mendekati tinggi.…”
Section: Siswa Mengalami Kesulitan Menyelesaikan Soal Matematika Kimiaunclassified
“…The MUST has consistently reported good reliability as it does in this study of 0.874 (the less stringent Cronbach's alpha = 0.875). The practical use of the MUST is well-established by the NSA Team [6][7][8][9], and its use documents that students' enteringautomaticity skills (what they can do mathematically without a calculating device) is a valid predictor of how successful they will be in Chem I and Chem II.…”
Section: Diagnostic Instrumentmentioning
confidence: 99%
“…While some students self-identified as non-binary for gender, this group was too small to report on while maintaining confidentiality. Previous studies by the Networking for Science Advancement (NSA) team have reported that students' automaticity ability (what can be done without the aid of a calculating device), as measured by an easily administered diagnostic test named the MUST (Math-Up Skills Test), correlates well with students' success in general chemistry courses (Albaladejo et al, 2018;Mamiya et al, in press;Petros et al, 2017;Powell et al, 2020;Villalta-Cerdas et al, in press;Weber et al, 2020;Williamson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the MUST has consistently reported good reliability as it does in this study of 0.874. The practical use of the MUST has been well-established by the NSA Team(Petros et al, 2017;Albaladejo et al, 2018;Williamson et al, 2020;Powell et al, 2020), and its use in these research studies documents that students' entering-automaticity skills are valid predictors of how successful they will be in Chem I and Chem II. Each student's MUST score was a sum of the correct items on a scale of 0 to 20.…”
mentioning
confidence: 99%